The English interpret St. Paul’s Epistle to the Romans chapter thirteen: from God save the king to God help the king, 1532 – 1649 - Atchison, Liam Jess (Kansas State University, 2007)
In England, 1532‐1649 was an era during which questions about obedience to rulers dominated ethical discussions. Most English people also respected biblical authority for governing certain behaviors. Obedience was central to the monarchy’s survival and the Bible was central to reformation of an English Church laden with medieval accretions. St. Paul’s Epistle to the Romans 13:1‐7 was the most important biblical passage for understanding the Christian’s relationship to civil authority during this period, and interpreters had such high regard for biblical authority that the backing of this passage was crucial to the acceptance of any political theory that involved ideas about obedience or disobedience. Though eisegesis was not out of the question as a technique among these interpreters, societal and political circumstances motivated most exegetes to examine the text more closely than they might have if St. Paul’s meaning had been irrelevant. These conditions led to creative handling of the text that permitted the exegetes to continue to submit to biblical authority while advocating their varied opinions on obedience to civil authority. Some interpreters moved outside the constraints of traditional views of monarchy and obedience to develop a theory that God mediated his call to rulers through those who elected them. Acceptance of this theory finally brought about rejection of divine right monarchy, as symbolized by the execution of Charles I in 1649. By too quickly concluding that these English expositors merely sought biblical justification for their views after the fact, scholars have failed to appreciate how Romans 13 positively shaped Reformation views of the Christian’s relationship to the state. As the title suggests, this study will examine the discernable shift from seeing Romans 13:1‐7 as a text that commands non‐resistance to rulers to one that not only permits disobedience, but requires it. Thus, Romans 13 is not simply an influential political text, but stands as the most important political text of the period under consideration. This dissertation supplies a needed analysis of representative exegesis of Romans 13:1‐7 during this critical period of English history and considers the influence of these expositions on the development of republian ideals.
Keywords: English Reformation; obedience; Romans 13; hermeneutics; resistance theories; biblical interpretation; History, Church (0330); History, European (0335)